Organizational behavior - Robbins, Stephen P., 1943- (Upper Saddle River, NJ : Pearson Prentice Hall, 2005)
'Organizational Behavior' contains new material on responding to global and cultural diversity with discussions of globalization, workforce diversity and ethics. There is an additional chapter on leadership and expanded coverage of interpersonal and behavioral skills.
Ch. 1. What is organizational behavior? -- Ch. 2. Foundations of individual behavior -- Ch. 3. Values, attitudes, and job satisfaction -- Ch. 4. Personality and emotions -- Ch. 5. Perception and individual decision making -- Ch. 6. Basic motivation concepts -- Ch. 7. Motivation : from concepts to applications -- Ch. 8. Foundations of group behavior -- Ch. 9. Understanding work teams -- Ch. 10. Communication -- Ch. 11. Basic approaches to leadership -- Ch. 12. Contemporary issues in leadership -- Ch. 13. Power and politics -- Ch. 14. Conflict and negotiation -- Ch. 15. Foundations of organization structure -- Ch. 16. Organizational culture -- Ch. 17. Human resource policies and practices -- Ch. 18. Organizational change and stress management -- App. A. Research in organizational behavior -- App. B. Careers and career development -- Skill-building modules.
Various multi-media instructional materials are available to supplement the text.
Includes bibliographical references and indexes.
Keywords: Organizational behavior; Comportement organisationnel; Organizational behavior; Organisationsverhalten; Organisatiegedrag; Management; Organisatiekunde; Organizational behavior